Adipocyte Oncostatin Receptor Regulates Adipose Tissue Homeostasis and Inflammation - Sanchez-Infantes, David; Stephens, Jacqueline M. (Frontiers in Immunology, 2021)
Adipocytes, or fat cells, are the largest cell type in adipose tissue, and they are known contributors to systemic metabolic health. Obesity, defined by excess adipose tissue (AT), is recognized as a low-grade chronic inflammatory state. Typically, in obesity, white adipose tissue (WAT) expansion beyond its normal capacity results in AT inflammation and systemic metabolic dysfunction. In addition to serving as a fuel reservoir, adipocytes are the sole source of specific endocrine hormones that play central roles in lipid storage and metabolism. AT is now also recognized as an immunological organ, and many studies have described the obesity-associated infiltration and proliferation of immune cells in a variety of fat depots in mice and humans. AT immune cells secrete a variety of chemokines and cytokines that act in a paracrine manner on adjacent adipocytes. Many of these paracrine mediators, including TNF, IL-6, and MCP-1, have been well studied in AT inflammation. Oncostatin M (OSM) is a proinflammatory cytokine that is elevated in AT in human obesity, and its specific receptor (OSMR) is also more highly expressed in conditions of obesity and insulin resistance. This review summarizes the biological role of oncostatin M receptor (OSMR) as a modulator of adipocyte function and a contributor to immunological alterations in AT in metabolic disease states.